2013
DOI: 10.2334/josnusd.55.29
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of satisfaction and complications in patients with existing complete dentures

Abstract: The aim of this clinical trial was to assess satisfaction, as well as the frequency and type of prosthetic complications in terms of several variables, in patients with complete dentures that had been supplied at private clinics. The study subjects were 64 patients with a mean age of 63.48 years wearing complete dentures provided at private clinics, and requesting new ones. The degree of patient satisfaction with their dentures was assessed, as well as complications and parameters related to the dentures such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 31 publications
3
38
0
13
Order By: Relevance
“…They also guide clinicians to make the best clinical judgment and pave their way to deliver prosthodontic treatment of high standards; however, studies that assessed quality of clinical procedures and standards of technical work in prosthodontics indicated unsatisfactory findings among a considerable proportion of the examined cases . Furthermore, a large number of studies reported failure of prosthetic dental restorations and associated complications . What can be noted following a review of such studies is that only the incidence and characteristics of failure were reported.…”
Section: Standards Of Care and Malpractice In Prosthodontics—an Overvmentioning
confidence: 99%
“…They also guide clinicians to make the best clinical judgment and pave their way to deliver prosthodontic treatment of high standards; however, studies that assessed quality of clinical procedures and standards of technical work in prosthodontics indicated unsatisfactory findings among a considerable proportion of the examined cases . Furthermore, a large number of studies reported failure of prosthetic dental restorations and associated complications . What can be noted following a review of such studies is that only the incidence and characteristics of failure were reported.…”
Section: Standards Of Care and Malpractice In Prosthodontics—an Overvmentioning
confidence: 99%
“…A study evaluated problems faced by patients post denture insertion. The most common complaint was inability to chew appropriately, and when the denture was examined, it was short of retention, which is a possible cause for dissatisfaction for both dentist and patients (9). Hence, the present study showed that, nevertheless, a weak but positive correlation existed between the quality and extension of the denture and patient's aesthetic, mastication, and phonetics (p<0.05).…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, saliva and other systemic conditions also play an important role (8). Bilhan et al concluded that 85% of patients lack denture retention, whereas the highest mean satisfaction score for speech was 77.27 ± 29.04 (9). It becomes a challenging task when the patient's expectation exceeds the patient's satisfaction regardless of the denture quality.…”
Section: Introductionmentioning
confidence: 99%
“…Ziarniniak szczelinowaty jest zmianą o charakterze łagodnym, jednak w każdym przypadku powinien być diagnozowany w kierunku wykluczenia rozrostu nowotworowego. [1][2][3][4][5][6][7][8][9] Podstawową zasadą rehabilitacji protetycznej jest zapobieganie urazom podłoża protetycznego. 1 W profilaktyce powstania ziarniniaka szczelinowatego kluczowym elementem postępowania jest prawidłowe zaprojektowanie i wykonanie protez, a szczególnie czynnościowe ukształtowanie obrzeża ruchomych uzupełnień protetycznych.…”
Section: Wprowadzenieunclassified
“…Najczęściej spotykaną patologiczną zmianą o charakterze rozrostowym na błonie śluzowej jamy ustnej jest ziarniniak szczelinowaty (granuloma fissuratum). 3,5,6 Zmiana ta występuje średnio u 5-14% użytkowników protez ruchomych. 3 Obserwacje kliniczne wykazały, że fałdy włókniste nie są przyczyną dolegliwości bólowych, wykrywane są przypadkowo, podczas wizyty stomatologicznej.…”
Section: Dyskusjaunclassified